2019
DOI: 10.9734/jpri/2019/v31i530310
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Patterns in a University Hospital in Al-Kharj City

Abstract: Introduction: Antibiotics are medications that are used to kill a bacterium which causes different infections. The misuse of these medications has contributed to the development of bacterial resistance. In order to predict the efficacy of the antimicrobial drugs and to guide antimicrobial therapy, antibiogram should be used. Objective: This study aims to explore the Antibiotic resistance patterns in a university hospital in AL-kharj city. Methods: Data from a university hospital in Al-Kharj city we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[17] Ahmed and Khan conducted a study in a university hospital in Al-Kharj and reported that the most common bacteria were E. coli (26.58%) followed by K. pneumoniae (16.45%), Enterococcus faecalis (13.92%), P. aeruginosa (12.65%), and S. aureus (12.65%). [18] Ahmed et al stated that in a public hospital in Al-Kharj, ESKAPE pathogens (Enterococcus faecium, S. aureus, K. pneumoniae, Acinetobacter baumannii, P. aeruginosa, and Enterobacter) cause nearly half of the infections that were caused by bacteria and the most common ESKAPE pathogen was K. pneumoniae followed by P. aeruginosa. [19] The SSI rate in the present study was 2.32%.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Ahmed and Khan conducted a study in a university hospital in Al-Kharj and reported that the most common bacteria were E. coli (26.58%) followed by K. pneumoniae (16.45%), Enterococcus faecalis (13.92%), P. aeruginosa (12.65%), and S. aureus (12.65%). [18] Ahmed et al stated that in a public hospital in Al-Kharj, ESKAPE pathogens (Enterococcus faecium, S. aureus, K. pneumoniae, Acinetobacter baumannii, P. aeruginosa, and Enterobacter) cause nearly half of the infections that were caused by bacteria and the most common ESKAPE pathogen was K. pneumoniae followed by P. aeruginosa. [19] The SSI rate in the present study was 2.32%.…”
Section: Discussionmentioning
confidence: 99%
“…doctors' offices and emergency departments, at least 28% of antibiotic courses prescribed annually are unnecessary, which makes improving the prescribing and the use of antibiotics a national priority [1].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the resistance rate of Klebsiella pneumonia was high only to ampicillin (susceptibility rate=1%) and Nitrofurantoin (susceptibility rate=37%). The resistance Ahmed and Khan reported that in a University Hospital in Al-Kharj, the most common bacteria were Escherichia coli (26.58%), Klebsiella pneumonia (16.45%) and that the percentages of Enterococcus faecalis, Pseudomonas aeruginosa and Staphylococcus aureus were 13.92%, 12.65% and 12.65% respectively 14. Moreover, Masoud et al found that Najran Area, the most prevalent bacteria isolated were Escherichia coli (35.63%), Klebsiella pneumoniae (18.08%), and Staphylococcus aureus (14.89%).…”
mentioning
confidence: 99%